2020
DOI: 10.21769/bioprotoc.3529
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Unicellular Recordings and Hippocampal-dependent Innate Behaviors in an Adolescent Mouse Model of Alzheimer’s disease

Abstract: Transgenic mice have been used to make valuable contributions to the field of neuroscience and model neurological diseases. The simultaneous functional analysis of hippocampal cell activity combined with hippocampal dependent innate task evaluations provides a reliable experimental approach to detect fine changes during early phases of neurodegeneration. To this aim, we used a merge of patch-clamp with two hippocampal innate behavior tasks. With this experimental approach, whole-cell recordings of CA1 pyramida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
(14 reference statements)
2
3
0
Order By: Relevance
“…We also found that this reduction in the induction of epileptic activity correlated with pTau's MD accumulation in PCs [ 92 ]. Collectively, our results provide support for the alternative role of pTau protein during normal physiological conditions and early stages of AD development [ 7 , 13 , 14 , 92 , 93 ]. Importantly, it was reported that during the early stage of AD development, phosphorylation of Tau protein at its site Thr205 alleviated A β -induced neuronal death and provided protection from excitotoxicity [ 16 ].…”
Section: Classical Tau Hypothesis Versus New Hypothesissupporting
confidence: 68%
See 4 more Smart Citations
“…We also found that this reduction in the induction of epileptic activity correlated with pTau's MD accumulation in PCs [ 92 ]. Collectively, our results provide support for the alternative role of pTau protein during normal physiological conditions and early stages of AD development [ 7 , 13 , 14 , 92 , 93 ]. Importantly, it was reported that during the early stage of AD development, phosphorylation of Tau protein at its site Thr205 alleviated A β -induced neuronal death and provided protection from excitotoxicity [ 16 ].…”
Section: Classical Tau Hypothesis Versus New Hypothesissupporting
confidence: 68%
“…Thus, from the classical point of view, all the data argued so far could favor the existence of a toxic cascade of A β 42-pTau/synaptic damage/network dysfunction. However, we firmly believe that our data, along with recently published data, will help to unveil a new hypothesis in which Tau phosphorylated near the MD could have a protective role during the early stages of AD development [ 13 16 , 29 , 92 , 93 ]. One molecular basis for this alternative hypothesis is that pTau protein at MD sites is physiologically located at the synaptic terminals [ 13 , 14 , 29 ].…”
Section: Classical Tau Hypothesis Versus New Hypothesissupporting
confidence: 62%
See 3 more Smart Citations